Impact of Tourism in the Local Economy of Bhaktapur - Shahi, Bijay Kumar (Nepal Tourism and Development Review, 2013)
This paper outlines the major aspects of tourism in Bhaktapur. The focus is to describe how tourism influences the economy of Bhaktapur. Bhaktapur is one of the famous tourist destinations in Nepal. As it is just 11.2 km away from Kathmandu, it is recognized by travels and tours operators as a half-day sightseeing package. Many tourists also prefer staying in Bhaktapur as it is comparatively cleaner and more peaceful than Kathmandu. The fact that Bhaktapur lies on the way to various other famous tourist hot-spots such as Nagarkot and Dhulikhel has also helped to increase tourism in Bhaktapur. Major attractions of Bhaktapur famous among tourists include Taumadhi Square, Durbar Square, Pottery Square, and Dattatreya Square. Besides, there are various other places which, if promoted, can become famous among tourists. DOI: http://dx.doi.org/10.3126/ntdr.v2i1.7383 Nepal Tourism and Development Review Vol.2(1) 2012 141-147